Comparison of physician referral and insurance claims data-based risk prediction as approaches to identify patients for care management in primary care: an observational study - Freund, Tobias; Gondan, Matthias; Rochon, Justine; Peters-Klimm, Frank; Campbell, Stephen; Wensing, Michel; Szecsenyi, Joachim (BMC family practice, 2013)
Primary care-based care management (CM) could reduce hospital admissions in high-risk patients. Identification of patients most likely to benefit is needed as resources for CM are limited. This study aimed to compare hospitalization and mortality rates of patients identified for CM either by treating primary care physicians (PCPs) or predictive modelling software for hospitalization risk (PM).
Gesehen am 17.05.2021